Advances in diagnosis, treatment, and prevention of invasive Salmonella infections. Issue 5 (October 2016) - MacFadden, Derek R.; Bogoch, Isaac I.; Andrews, Jason R.
Abstract : Purpose of review: Typhoidal and nontyphoidal Salmonella enterica serotypes are among the most common bacterial causes of acute febrile illnesses in the developing world. In this review, we discuss new advances in understanding of the burden, diagnostic approaches, treatment and vaccines for invasive Salmonella infections. Recent findings: Recent estimates of the global burden of typhoidal and nontyphoidal Salmonella not only affirm the importance of these infections but also highlight the paucity of systematic incidence data from many regions. New data from Africa indicate that typhoidal Salmonella may be more common than previously considered. Novel diagnostic techniques for Salmonella include new serologic, molecular and metabolomic approaches, but blood culture – although slow and insensitive – remains the primary means of establishing a diagnosis. Antibiotic resistance, particularly to fluoroquinolones, continues to emerge and threatens to undermine treatment success for these infections. New vaccines for typhoid, including conjugate vaccines with longer duration of immunity than prior vaccines, represent a promising tool for prevention of enteric fever. Summary: Invasive Salmonella infections are a major cause of morbidity and mortality worldwide. Increasing antibiotic resistance in Salmonella is concerning, and empiric oral options are being rapidly eroded. Where new effective antimicrobials are lacking, developments in vaccines offer hope for reducing the burden of Salmonella infections globally.